Rural telephony: VoIP in the wilderness - Dada, John (Technical Centre for Agricultural and Rural Cooperation, 2008)
With no fixed-line service and mobile phone operators reluctant to invest in rural areas, the Fantsuam Foundation decided to provide VoIP to customers on its wireless network in northern Nigeria.